Learners’ motivational styles and their impact on instructional designs of second language/ Hamit Haji Aini - Haji Aini, Hamit (2004)
This study undertaken is indeed an effort to find out whether motivation identified as instrumental and integrative motivation exist among the students of SMB ST. THOMAS a secondary school in the middle of town Kuching Sarawak. The prime interest of the researcher is to find out the impact of those motivational styles on their preference for teachers’ instructional designs in second language learning. Three instructional designs have been identified namely traditional orientation, communicative orientation , and integrated orientation.